2021
DOI: 10.2478/ngoe-2021-0023
|View full text |Cite
|
Sign up to set email alerts
|

A Demand-Side Analysis of Intellectual Capital in the Accommodation Industry: The Case of the Youth Market in Slovenia

Abstract: To date, research on intellectual capital (IC) in tourism has dealt with the supply-side view. This study continues the research into IC and develops a new perspective dealing with the demand side of IC in the accommodation industry, focusing on young consumers. On the theoretical ground, the study adapts the supply-side IC indicators to the demand-side perspective. A convenience sampling approach is used, and data was collected from 150 students representing the youth market. Exploratory factor analysis (EFA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…Intellectual capital is the knowledge, intellectual property, information, analytical skills, competencies, and skills of an organization's employees to create a competitive advantage. Several studies have demonstrated that intellectual capital affects the performance of hospitality firms (Bontis et al, 2015;Cuevas-Vargas et al, 2019;Haliq et al, 2018;Rudež, 2021;Zeglat & Zigan, 2013). According to Anggraini et al (2018a), intellectual capital consists of human capital (HC), such as knowledge; structural capital (SC), such as information and communication systems; and relational capital (RC), such as partnerships with stakeholders and has been demonstrated to affect business performance.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
See 4 more Smart Citations
“…Intellectual capital is the knowledge, intellectual property, information, analytical skills, competencies, and skills of an organization's employees to create a competitive advantage. Several studies have demonstrated that intellectual capital affects the performance of hospitality firms (Bontis et al, 2015;Cuevas-Vargas et al, 2019;Haliq et al, 2018;Rudež, 2021;Zeglat & Zigan, 2013). According to Anggraini et al (2018a), intellectual capital consists of human capital (HC), such as knowledge; structural capital (SC), such as information and communication systems; and relational capital (RC), such as partnerships with stakeholders and has been demonstrated to affect business performance.…”
Section: Literature Review and Hypotheses Formulationmentioning
confidence: 99%
“…Human capital (HC) is defined as employees' knowledge, competencies, workrelated attitudes, and capacity for innovation (Rudež, 2021). According to Cuevas-Vargas et al (2019), elements of human capital for hospitality organizations, such as employee competence, attitude, and innovation, are crucial because they can generate new consumer values.…”
Section: H1: Intellectual Capital Affects Business Performancementioning
confidence: 99%
See 3 more Smart Citations